Medicinal plants having a dual role in treating both human and livestock diseases in Suro Barguda District, West Guji Zone, Southern Ethiopia - Eshete Ashagre Mersha
This study aimed to identify and analyze medicinal plants used by the Guji Semi-Pastoralist People in Suro Barguda District, West Guji Zone, and Southern Ethiopia. 124 informants with knowledge of traditional herbs were interviewed, and ethnobotanical data was collected. 22 medicinal plant species were identified, with Euphorbiaceae, Rubiaceae, Rutaceae, Apiaceae, and Solanaceae being the most common. Oral application was the most popular method, and herbal medicines were often made using freshly harvested plant parts. The high-use value indices of multipurpose plant species identified in the research area provide indicators of high use pressure and keys to developing and executing complementing in situ and ex situ conservation interventions to maintain these highly used plant species.